Christian Perspectives on Environmental Stewardship and Their Influence on Sustainable Living Practices - Jacob, Yessy Kenny (Arbain Publishing, 2025)
This study explores Christian perspectives on environmental stewardship and examines their influence on sustainable living practices among believers. Utilizing a qualitative methodology through library research, the study draws upon theological literature, scriptural interpretation, and contemporary scholarly works to analyze how Christian beliefs inform environmental ethics and behaviors. The research investigates key biblical principles such as dominion, creation care, and stewardship, and how these concepts have been interpreted within various Christian traditions. Particular attention is given to how these theological views inspire practical engagement with sustainability, including lifestyle choices, advocacy, and community involvement in ecological initiatives. Through a critical analysis of theological writings and environmental discourses within Christian contexts, the study identifies both congruence and tension between faith-based teachings and contemporary ecological challenges. The findings suggest that Christian theology, when framed around responsible stewardship rather than exploitative dominion, can provide a strong moral and spiritual foundation for sustainable living. Moreover, denominational differences, cultural contexts, and levels of theological engagement significantly influence how environmental stewardship is understood and practiced. This research contributes to the growing body of literature on religion and ecology by highlighting how faith-based frameworks can support global efforts toward environmental sustainability. The study concludes by recommending further interdisciplinary dialogue between theology, environmental science, and policy to enhance faith-driven ecological awareness and action.